A revolução azul das mulheres - Igualdade de gênero na aquicultura - Marques, Flavielle Blanco; Hellebrandt, Luceni; Miranda, Letícia; Cavalli, Lissandra Souto (Pesquisa Agropecuária Gaúcha, 2018)
The permanent rapid spread and evolution of aquaculture is called the blue revolution (KRAUSE et al., 2014). The blue revolution which brings adequacy requirements for best practices regarding environmental and social practices, sustainable business and work safety (LEE, 2015), nevertheless gender issues were not addressed. Even in small-scale, women work is frequently unrecognized, under or unpaid (WILLIAMS et al., 2010). The aquaculture industry, as well as the academic world related to this activity, has been traditionally dominated by men (ARENSBERGEN et al., 2012 ).